PENGARUH KECEMASAN IBU TERHADAP PROSES PERSALINAN KALA 1 FASE AKTIF DI BPS ATIK SUHARIJATI SURABAYA - Nur Masruroh (Universitas Nahdlatul Ulama Surabaya, 2015)
The relationship with the mother's level of anxiety in the first stage of labor active phase in BPM Atik Suharijati Surabaya. Mothers who experienced the process of labor is a physiological thing, but in reality people still think childbirth is a life and death stakes. Mothers who give birth experience anxiety levels cause birth becomes pathological. This study aims to determine the relationship with the mother's level of anxiety in the first stage of labor active phase in BPM Atik Suharijati Surabaya. Design analytical research with cross sectional approach. The population around the third trimester pregnant women who face labor in BPS Atik Suharijati in April-May 2015 of 25 respondents. A sample of 12 respondents in October was taken with the technique of